Pemeriksaan Selaput Dara Dari Perspektif HAM - Sasongko, Purwanto Panji (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
Hymen examination is synonymous with the 'virginity test' which is a controversial examination by medical professionals. One of the famous myths about virginity is that 'virginity' is proven by writing the appearance of